Total quality management practices among staff in district education offices in Negeri Sembilan / Ain Nathasha Omar - Omar, Ain Nathasha (2014)
The purpose of this study was to determine the awareness of Total Quality Management on Deming 14 points among District Education Office staff, to determine any significant differences of perception on Quality Management of Deming 14 points based on demographic factors among District Education Office staff and to identify the relationship between dimensions of Quality Management of Deming 14 points. The finding clearly shows that the importance of quality management service to improve the quality standard in District Education Office services. The result of this study was benefited to both schools and district leaders to develop strategies to improve the academic performance level of schools. Descriptive-correlational method consists of quantitative and qualitative techniques were used during the investigation. The findings revealed that the levels of the fourteen dimensions in 14-Deming Points namely leadership, vision, actors, employee employment, policy strategy and culture, process control and improvement, continuous improvement, recognition and reward, program design and other stakeholder focus was at moderate and high mean score categories. The awareness and perception towards Total Quality Management overall result for six districts at Negeri Sembilan were identified at the moderate level.